PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KETERAMPILAN MENJAHIT DI DESA LAMBANG SARI IV KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Mega Tamara F; Sumardi Sumardi; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Studies examined the sewing skills performed in the community empowerment program in the Village Lambang Sari IV District Lirik Regional Indragiri Hulu and empowerment there are priciples, purposes, stages and steps in performing community empowerment through sewing skill. The purpose of this study is to improve education levels, improve accessibility. To improve actions, to improve businesses and to improve people’s incomes. Public empowerment is also aimed at improving the quality of community independence by providing adaptive education such as needlepoint sewing this type of research is a deductive to a qualitative approach, a complex data collection process is conducted: by interviewing the research subjects of 1 core informant and 2 control informant with the documented. Based on the interview. The research found 3 indicators of (1) execution, (2) relevance and (3) the participation of the study off all 3 of the these indicators is helpful in understanding how the appropriate phase of process of executing is done. Comunnity empowerment through sewing skills.Key Words: Community Empowerment, Sewing Skills